The era of RNA interference medicines: the clinical landscape of synthetic gene silencing drugs - Godinho, Bruno (2020)
ABSTRACT - Therapeutic oligonucleotides, such as small interfering RNAs (siRNAs), provide a simple and effective tool to modulate the expression of any gene. siRNAs harness the RNA interference (RNAi) pathway to degrade disease-associated messenger RNAs (mRNAs). The inherent sequence specificity and potency of siRNAs makes them ideal drug candidates that are expected to transform drug development and our approach to human health. However, the first wave of clinical trials was not immediately successful and temporarily dampened the excitement over this newly discovered technology. Most studies did not meet the desired efficacy and failed to achieve clinically-relevant endpoints. Poor chemical design, lack of enzymatic stability and inadequate delivery strategies were found to be the main issues stifling success. Recent advancements in RNA chemistry, biology, and mechanistic understanding of factors that define oligonucleotide pharmacokinetic/pharmacodynamic behavior have resulted in a fundamental shift in the clinical landscape of this novel class of therapeutic modalities. As a result, there has been a dramatic increase in both the numbers of clinical trials and, more importantly, the level of observed clinical efficacy. In 2018, we witnessed a major landmark for the field with the first RNAi-based therapeutics, Patisiran (OnpattroTM), being approved by the Food and Drug Administration and the European Medicines Agency. Several other lead compounds have achieved unprecedented levels of activity following a single treatment dose, and hold great promise as new therapeutic strategies for liver diseases. This review gives an overview of the clinical landscape of synthetic RNAi drugs, contextualizing how advances in RNAi chemistry and formulation strategies have helped define the clinical utility of this promising class of drugs.